Becoming Moderate Muslims: The Role and Dynamics of Strengthening Religious Moderation in Religious Moderation Houses (RMB) STAIN Majene and UIN Datokarama Palu - Usman, Muhammad Ilham; Aldiawan, Aldiawan; Adawiah, Rabiatul (Jurnal Adabiyah, 2025)
This study analyzes the role and dynamics of the Rumah Moderasi Beragama (RMB) at STAIN Majene and UIN Dato Karama in promoting moderate Muslims within academics and society. Data were collected through observation, interviews, and documentation. The research was conducted over five months, involving the heads and secretaries of the Rumah Moderasi Beragama (RMB), instructors, lecturers, academic staff, and students as informants. Applying the theory of religious moderation and Imre Lakatos’ Scientific Research Programmes reveals that establishing RMBs in Islamic higher education institutions (PTKIN) is essential and serves as a pillar for sustaining the discourse of religious moderation in Indonesia. Imre Lakatos states that a program will persist and remain progressive if supported by three key factors despite opposition: hard-core, protective belt, and heuristics. These three supporting factors have been implemented in the activities of RMB at STAIN Majene and UIN Dato Karama Palu. The hard core consists of fundamental principles that cannot be changed, such as tolerance, commitment, non-violence, and the acceptance of local traditions. The protective belt is reflected in various activities carried out by RMB, such as seminars, workshops, socialization programs, and training sessions on moderation for students, staff, and lecturers. Meanwhile, heuristics can be observed in several programs, such as introducing religious moderation to new students on campus and sending trainers to participate in Training of Trainers programs. الملخص هذا البحث يهدف الى تحليل الدور والدينامكي البيت الوسطية الدينية (ر م ب) فى المعهد العالى للدراسات الإسلامية الحكومية ماجينى والجامعة الإسلامية الحكمية داتوكارماه فى الترويج المسلمون المعتدلون بين الأكاديميين والمجتمع. البيانات التى تم جمعها من خلال الملاحظ والمقابلة والوثيقة. هذا البحث يتم إجرئه لمدة خمسة أشهر من خلال إشراك الرئيس وسكرتير من البيت الوسطية الدينية (ر م ب) ومرشد ومعلم والطاقم الأكاديمي والطلاب كمخبر. إستخدام النظرية الوسطية الدينية وبرنامخ بحث  (Scientific Research Programs) إمري لاكاتوش, هذا البحث يمكن أن يظهرأنّ التأسيس (ر م ب) فى الكلية الدينية الإسلامية الحكومية يكون الشيء الذى مهم جدا ويصبح عمود لإستدامة خطاب عن الوسطية الدينية في أندونيسيا. قال إمري لا كاتوش أن برنمج سوف يبقى على قيد الحياة ويظل تقديما إذاكان مدعوما بثلاثة عوامل الرئيسية علي الرغم من التحديات: النواة الصلبة(hard core) , حزام واق(protective belt) , و مساعد كشف(heuristic) . وقد تم تنفيذ على هذه العوامل فى الأنشطة على المعهد العالى للدراسات الإسلامية الحكومية ماجيني وجامعة الإسلامية الحكومية داتوكارماه بالو. النوة الصلبة يتكون من المبادئ الأساسية التي لايمكن تغييرها مثل التسامح والإلتزام ومناهضة العنف وقبول التقاليد اللمحلية. حزام واق ينعكس فى مختلفة الأنشطة الذي يفعل الموظفون مثل الندوات وورش العمل وبرامج التنشئة الإجتماعية وتدريب الوسطية للطلاب والمعلم. في الوقت نفسه مساعد كشف يمكن ملاحظته فى العديد من البرامج مثل تقديم الوسطية الدينية على الطلاب الجديد ويرسل المدرب للمشاركة فى برنامج تدريب المدبين Abstrak Penelitian ini bertujuan untuk menganalisis peran dan dinamika Rumah Moderasi Beragama (RMB) di STAIN Majene dan UIN Dato Karama Palu dalam mempromosikan Muslim moderat di kalangan akademisi dan masyarakat. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Penelitian ini dilakukan selama lima bulan, dengan melibatkan ketua dan sekretaris Rumah Moderasi Beragama (RMB), instruktur, dosen, staf akademik, dan mahasiswa sebagai informan. Dengan menggunakan teori moderasi beragama dan Scientific Research Programs Imre Lakatos, penelitian ini menunjukkan bahwa pendirian RMB di Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) merupakan hal yang sangat penting dan menjadi pilar bagi keberlangsungan wacana moderasi beragama di Indonesia. Imre Lakatos menyatakan bahwa sebuah program akan bertahan dan tetap progresif jika didukung oleh tiga faktor kunci meskipun mendapat tentangan: hard-core, protective belt, dan heuristik. Ketiga faktor pendukung ini telah diimplementasikan dalam kegiatan RMB di STAIN Majene dan UIN Dato Karama Palu. Hard core terdiri dari prinsip-prinsip dasar yang tidak dapat diubah, seperti toleransi, komitmen, anti kekerasan, dan penerimaan terhadap tradisi lokal. Protective belt tercermin dari berbagai kegiatan yang dilakukan oleh RMB, seperti seminar, lokakarya, program sosialisasi, dan pelatihan moderasi bagi mahasiswa, staf, dan dosen. Sementara itu, heuristic dapat diamati dalam beberapa program, seperti memperkenalkan moderasi beragama kepada mahasiswa baru dan mengirimkan pelatih untuk berpartisipasi dalam program pelatihan untuk pelatih.